2023
DOI: 10.21203/rs.3.rs-2357036/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing genomes recovered from time-series metagenomes using long- and short-read sequencing technologies 

Abstract: Background Over the past years, sequencing technologies have expanded our ability to examine novel microbial metabolisms and diversity previously obscured by isolation approaches. Long-read sequencing promises to revolutionize the metagenomic field and recover less fragmented genomes from environmental samples. Nonetheless, how to best benefit from long-read sequencing and whether long-read sequencing can provide recovered genomes of similar characteristics as short-read approaches remains unclear. Results W… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The sequencing depth for each MAG was estimated mapping the unassembled LRs using minimap2 v2.17 61 with the map-hifi option, and filtering mapped LRs at ≥ 95% identity using the jgi_summarize_bam_contig_depths script from MetaBAT v2.2.15 62 . These average sequencing depth values were normalized using the genome equivalents determined for each metagenome 27 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequencing depth for each MAG was estimated mapping the unassembled LRs using minimap2 v2.17 61 with the map-hifi option, and filtering mapped LRs at ≥ 95% identity using the jgi_summarize_bam_contig_depths script from MetaBAT v2.2.15 62 . These average sequencing depth values were normalized using the genome equivalents determined for each metagenome 27 .…”
Section: Methodsmentioning
confidence: 99%
“…The resulting read depth values were truncated to the middle 80% (TAD80) of depth values (i.e., the upper and lower 10% of outliers were removed) using a Python script from https://github.com/rotheconrad/00_in-situ_GeneCoverage 13,70 . Finally, to estimate the relative abundance with respect to the abundance of bacterial and archaeal communities, each TAD80 value was normalized by the "genome equivalents" value estimated using MicrobeCensus v1.1.0 27,71 .…”
Section: Metagenomes and Mags Recovery From Water Column Metagenomesmentioning
confidence: 99%
“…Promisingly, third-generation platforms will overcome some short-read sequencing limitations, mainly regarding highly repetitive regions, high levels of sequence microdiversity, multiple copies of genes, or AT-rich/GC-rich regions. 73,76,77 Finally, users must also be familiar with technical aspects such as the sequencing depth, which may greatly impact the resolution of the results. 78 Quince et al 78 reported that a fixed depth of 10 million reads and a minimum of 1 Gb sequencing per sample are typically used or recommended in metagenomic studies, but high levels of host DNA may interfere with an accurate reconstitution of the microbiome profile.…”
Section: Advantagesmentioning
confidence: 99%
“…PacBio HiFi sequencing produces highly accurate consensus reads (>Q20, median Q30) that are 10–20 kb in length (Wenger et al 2019). Several studies have demonstrated that HiFi sequencing generally produces more total MAGs and higher quality MAGs than short-read sequencing (Priest et al 2021; Gehrig et al 2022; Meslier et al 2022; Eisenhofer et al 2023; Orellana et al 2023; Tao et al 2023; Zhang et al 2023), and that HiFi sequencing outperforms ONT for metagenome assembly (Meslier et al 2022; Sereika et al 2022). The high accuracy of HiFi reads has led to the development of two new metagenome assembly methods, hifiasm-meta (Feng et al 2022) and metaMDBG (Benoit et al 2023), which perform better than previous methods such as HiCanu (Nurk et al 2020) and metaFlye (Kolmogorov et al 2020).…”
Section: Introductionmentioning
confidence: 99%